Exploring an Experienced EFL Teacher on Classroom Management: A Case Study on Motivational Skill - Apris Bella Ayu Anggraini; Budi Setyono; Bambang Arya Wija Putra (IJET (Indonesian Journal of English Teaching), 2024)
Classroom management is one of the essential teaching skills required to be mastered by teachers, and its goal is to develop a conducive academic and social-emotional learning environment. This article reported the research exploration of how an experienced senior high school English teacher manages her class to make the students feel comfortable and motivated to learn English in the classroom. This research was designed as qualitative case study research and collected the data by observing and recording the classroom learning session and voice recording interviews. The thematic analysis revealed that an experienced senior high school English teacher managed her class by applying course-specific, teacher-specific, and group-specific motivational components to make students feel comfortable and motivated. The findings imply that English teachers create exciting learning activities besides morning storytelling to make students feel comfortable and motivated. The teacher prepares more teaching media for the materials well and thinks about the time spent on every activity in the opening, primary, and closing activities (in case of an unpredictable event).